2012
DOI: 10.1002/ejoc.201101240
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene‐Labeled 1,2,3‐Triazole‐Linked Bispyridinium Amide for Selective Sensing of H2PO4 by Fluorescence and Gel Formation

Abstract: A new receptor 1 has been designed and synthesized for the selective recognition of anions, which employs hydrogen bonding and electrostatic interactions. Receptor 1 selectively recognizes H 2 PO 4 -to exhibit a ratiometric emission response and formed a stable gel in CHCl 3 that contained 10 % CH 3 CN, which is useful to visually sense H 2 PO 4 -. In compari-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The other anions gave only small changes in emission, so the determination of association constants was not possible. Interestingly, receptor 46 formed a stable gel in CHCl 3 with 10 % acetonitrile in the presence of [H 2 PO 4 – ] 71…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other anions gave only small changes in emission, so the determination of association constants was not possible. Interestingly, receptor 46 formed a stable gel in CHCl 3 with 10 % acetonitrile in the presence of [H 2 PO 4 – ] 71…”
Section: Applicationsmentioning
confidence: 99%
“…Gel phases have been also obtained as a result of an anion recognition process. For instance, Ghosh et al have reported evidence of thermoreversible gel phase formation occurring in a binary CH 3 CN/CHCl 3 (90:10) mixture after the addition of two equivalents of Bu 4 NH 2 PO 4 to receptor 46 (Scheme ) 71. Atomic force microscopy (AFM) investigation showed that the gel morphology was characterized by the presence of spherical aggregates.…”
Section: Applicationsmentioning
confidence: 99%
“…During our ongoing effort in the area of supramolecular chemistry research, we have used the different simple heterocylic motifs (e. g., pyridinium,, benzimidazolium and benzimidazole, triazole etc.) in devising some useful molecular sensors for ionic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39] Therefore, the detection of H 2 PO 4 À selectively among other biologically relevant phosphates, such as adenosine monophosphate (AMP 2À ), adenosine diphosphate (ADP 2À ), and adenosine triphosphate (ATP 2À ), is very important. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] Recently,wereported an anthracenyl-appended triazole-linked receptor that was selective to Co 2 + . [54] Whent his receptor was quarternized at the triazole nitrogena toms,e ffective binding to biologically relevant triphosphateswas obtained.…”
Section: Introductionmentioning
confidence: 99%